Transition for patients with congenital heart disease in the UK: need for a universal model with adequate training and support. (25th November 2020) - Krishnathasan, K; Constantine, A; Fitzsimmons, S; Taliotis, D; Bedair, R; Curtis, S; Frigiola, A; Orchard, E; Pandya, B; Lockhart, C.J; Clift, P; Hudsmith, L; et al.
Abstract: Background: Adolescence is a vulnerable period for patients with congenital heart disease (CHD). Transition is a process that guides these patients through adolescence and ensures a smooth transfer to adult services, in order improve adherence to medical care and reduce loss to follow-up. While the importance of a formal Transition process is widely recognised and a requirement for specialist services in the UK, the optimal structure and delivery of Transition remains a matter of debate. Aims: To examine the different models of Transition currently in place in specialist CHD centres around the UK. Methods: A survey of Adult CHD centres in the UK was performed. A focus was placed on the structure of the Transition service, relevant training and areas of perceived improvement. Results: There were 10 responses to our survey covering 10 specialist CHD centres. All respondents were consultant adult CHD specialists, looking after patients from the age of 16 [14–17] years. All centres have a specialised Transition service, which runs from the age 13 [11–15] to 18 [16–25] years (duration of transition 5 [2–13] years). The majority of centres (80%) report providing transition care "well before" transfer to adult care, whereas 20% provide transition care at or immediately before transfer (i.e. first adult CHD appointment). Transition is delivered by physicians and clinical specialist nurses in approximately equal numbers in 9 (90%) centres and exclusively by clinical nurse specialists in 1 (10%) centre. A median of 2 [1–5] visits are planned for each patient, with 7 (70%) centres seeing patients at least twice during transition. The majority, but not all centres (70%) provide a health passport during transition. A significant number of centres felt they werer not receiving sufficient support in the following domains: financial (50%), training (30%), clinical space (30%), referrals from paediatrics (50%). All respondents felt that their Transition service had room for improvement. Other areas of improvement highlighted included reduction in loss to follow-up, difficulties in providing a Transition service to patients followed in peripheral hospitals, the need for more support from paediatric services in referring all appropriate patients, and dedicated administrative support. The vast majority of respondents (9, 90%) felt equipped with the appropriate skills to care for transition patients. However, few (2, 20%) had completed formal training in more than one area related to adolescent health and transition. Conclusions: While all CHD centres have a Transition service, Transition models and delivery differs significantly. There is urgent need for research in this area to develop a unified model, greater financial support and relevant training to optimise care. Funding Acknowledgement: Type of funding source: None